SEDIMENT CHARACTERISTICS OF BED LOAD TRANSPORT IN MAHAP RIVER OF NANGA MAHAP SUB-DISTRICT, SEKADAU REGENCY, INDONESIA - Ika, Anggraini Muthya; Zainal, Wahyu; Yufiansyah, Yufiansyah (Jurnal Teknik Sipil, 2022)
Sedimentation is a crucial factor when it comes to river problems. Sediment can cause silting of the river so that its capacity be reduced and can cause overflow of water to the surface. Every year, Districts of Nanga Mahap at Sekadau Regency always experiences flooding and the problem is still happening up until now. One of the causes of the occurrence of flooding in Nanga Mahap District is the overflow of the Mahap River. This study aims to determine the characteristics and rates of bottom sediment transport rate in the downstream of the Mahap River. Sediment collection was carried out on 8 segments of the estuary. In the study, laboratory tests were carried out regarding specific gravity and grain size of sediment particles refers to the texture classification by USDA (U.S. Department of Agriculture) and freight rate calculations Basic Sediment with Duboys Method. Based on characteristic analysis Mahap River sediments obtained the average D50 sediment grain diameter value from all research points that is equal to 1.63 mm, the results of testing the specific gravity the average obtained is 2.754 gr/cm3 so that it can be classified in the form of coarse grains with a type of sand sediment. The largest base sediment transport rate of bed load occurred at point 2 of 8.816 tons/day and the smallest was at point 7, which is 0.154 tons/day. From the calculation, result shows that if the velocity of falling particles is greater than the velocity of the flow of river water, therefor the sediment particles will settle.